2017
DOI: 10.1371/journal.pone.0184518
|View full text |Cite
|
Sign up to set email alerts
|

Perihematomal diffusion restriction as a common finding in large intracerebral hemorrhages in the hyperacute phase

Abstract: PurposeThere is growing evidence that a perihematomal area of restricted diffusion (PDR) exists in intraparenchymal hemorrhages (IPH) within 1 week of symptom onset (SO). Here, we study characteristics and the clinical impact of the PDR in patients with hyperacute (≤ 6 hours from SO) IPH by means of apparent diffusion coefficient (ADC).MethodsThis monocentric, retrospective study includes 83 patients with first-ever primary IPH from 09/2002-10/2015. 3D volumetric segmentation was performed for the IPH, PDR, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, a clinical study observed PHE with magnetic resonance imaging (MRI) in 56 of 83 patients with ICH within 6 hours after the onset of the disease. Subsequently, it attributed the restricted diffusion perihematomal area to transient oligemic and metabolic changes [ 27 ]. Using multimodal images including diffusion-weighted magnetic resonance imaging (DWI), apparent diffusion coefficient (ADC) maps, perfusion-weighted magnetic resonance imaging (PWI), and proton magnetic resonance spectroscopic (MRS) images, researchers also revealed that hypoperfusion in the perihematomal tissues might be caused by reduced metabolic demand (diaschisis) rather than ischemia [ 28 31 ].…”
Section: The Time Phase and Pathophysiology Of Phementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a clinical study observed PHE with magnetic resonance imaging (MRI) in 56 of 83 patients with ICH within 6 hours after the onset of the disease. Subsequently, it attributed the restricted diffusion perihematomal area to transient oligemic and metabolic changes [ 27 ]. Using multimodal images including diffusion-weighted magnetic resonance imaging (DWI), apparent diffusion coefficient (ADC) maps, perfusion-weighted magnetic resonance imaging (PWI), and proton magnetic resonance spectroscopic (MRS) images, researchers also revealed that hypoperfusion in the perihematomal tissues might be caused by reduced metabolic demand (diaschisis) rather than ischemia [ 28 31 ].…”
Section: The Time Phase and Pathophysiology Of Phementioning
confidence: 99%
“…Sur1-Trpm4, NKCC1, AQP4, the Na + -H + exchanger, and the Na + -Ca 2+ exchanger also drive the formation of cytotoxic edema [ 79 ]. Therefore, it is speculated that the imaging characteristics of PHE in patients may be similar to those of cytotoxic edema within 1-3 days [ 14 , 27 ]. However, as previously illustrated, ionic edema is also characterized by extravasation of ions and accumulation of extracellular fluid (similar to interstitial edema) [ 12 , 78 ].…”
Section: The Classification and Imaging Characteristics Of Phementioning
confidence: 99%
See 1 more Smart Citation